Torsional and compressive behaviours of a hybrid material: Spiral fibre reinforced metal matrix composite. (15th November 2015) - Khoddam, S.; Estrin, Y.; Kim, H.S.; Bouaziz, O.
Abstract: Armouring metals with strong wires or fibres is a common way of providing them with extra mechanical strength. A metal–metal composite armoured with twisted (spiral-shaped) wires is a particularly attractive option. We propose such a design that can be realised by twisting of a pre-assembled metallic matrix with embedded reinforcing fibres. An analytical model was developed to predict the torsional behaviour and the torque–twist requirements in the twisting stage to fabricate such a metal–metal hybrid material. Also, a semi-analytical multi-shell model was developed based on the upper bound theorem to estimate the plastic deformation behaviour of the hybrid material under axial compression. Samples of commercially pure Cu as the metallic matrix and stainless steel fibres as the reinforcing components were fabricated. A fair agreement of the experimental torque vs. twist data for torsional deformation and compressive load vs. stroke data of the compression test with the model predictions was found. The structural performance of the metal–metal hybrid showed an improvement of properties compared to the solid part without the fibres. Graphical abstract: Highlights: Fabricated metal–metal hybrids with spiral reinforcement by torsional deformation Proposed and verified two models of plastic response of such hybrid materials Demonstrated improved mechanical behaviour of the hybrid material due to fabrication